Explicit Expressions for Rapid Evaluation of APF in Variable-frequency Air Conditioners - Chen Xuancheng; Zhuang Dawei; Yu Yuefeng; Ding Guoliang (Zhileng xuebao)
The determination method for the annual performance factor (APF) of the air conditioner energy efficiency index given in the national standard involves a series of evaluations and nested calculations, and the process is complex. The objective of this study is to convert the APF calculation formulas given in the new National Standard GB 21455—2019 into explicit calculation expressions, meeting the requirements for convenient APF calculation. The adopted method is as follows: first, the four intermediate variables of the APF are simplified by directly substituting independent variables; then, the process of determining the calculation interval and segmental calculation is simplified by means of numerical fitting; finally, the APF explicit expressions are obtained by substituting the explicit expressions of the four intermediate variables into the APF definition. The developed APF explicit expressions apply to variable-frequency air conditioners with different rated cooling capacities with good accuracy. Based on the definition of the APF in the National Standard, the calculation errors of the explicit expression for the 5-test working conditions and 7-test working conditions are 0.73% and 1.17%, respectively.